Type of adjuvant endocrine therapy and disease-free survival in patients with early HR-positive/HER2-positive BC: analysis from the phase III randomized ShortHER trial - Maria Vittoria Dieci; Giancarlo Bisagni; Stefania Bartolini; Antonio Frassoldati; Roberto Vicini; Sara Balduzzi; Roberto D’amico; Pierfranco Conte; Valentina Guarneri (npj Breast Cancer, 2023)
Abstract The optimal adjuvant endocrine therapy for HR-positive/HER2-positive breast cancer patients is unknown. We included in this analysis 784 patients with HR-positive/HER2-positive BC from the randomized ShortHER trial of adjuvant trastuzumab (1 year vs 9 weeks) + chemotherapy. At a median follow-up of 8.7 years, patients who received AI had a significantly better DFS vs patients who received TAM or TAM-AI: 8-yr DFS 86.4 vs 79.7%, log-rank P = 0.013 (HR 1.52, 95% CI 1.09–2.11). In multivariate analysis, the type of endocrine therapy maintained a significant association with DFS (HR 1.64, 95% CI 1.07–2.52, p = 0.025 for TAM/TAM-AI vs AI). Among premenopausal patients aged ≤45 years, the use of GnRHa was associated with longer DFS: 8-yr DFS rate 85.2 vs 62.6% (log-rank p = 0.019, HR 0.41, 95% CI 0.19–0.88). In this post-hoc analysis of the ShortHER trial adjuvant treatment with AI was independently associated with improved DFS. Subgroup analysis in premenopausal patients suggests benefits with ovarian suppression. Trial registration: NCI ClinicalTrials.gov number: NCT00629278.